PENGAWASAN KELUARGA TERHADAP PENGENDARA MOTOR BERUSIA DI BAWAH 17 TAHUN DI SMP NEGERI 34 PEKANBARU TAHUN 2023/2024 - Azhari, Azhari; Baharuddin, Yulizar; Ali, Auzar; Bahri , Syamsul (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
This study aims to determine school supervision and parental supervision of motorcyclists in children under 17 years of age at 34 State Junior High Schools Pekanbaru. Data collection techniques include observation, questionnaires, and interviews. The population in this study amounted to 103 people and a sample of 41 people using Roscoe's opinion in Sugiono (2011.90) which said that 40% of the total population was taken. The results showed that the age of parents who allowed their children to ride motorbikes was 36-40 years old with the most education levels being high school and their work as housewives (not working). Family supervision of children who ride motorbikes in children under 17 years old, namely parents always provide advice and direction to children and are always responsible for violations committed by children, parents take action against children who ride motorbikes during school learning hours and parents also separate pocket money and gas money for the child. Violations that have been committed by children, such as fighting the current and riding a motorcycle at high speed, violating traffic signs, not equipping a vehicle and not wearing a helmet. Keywords: School Supervision, Family, Motorcyclists